2013
DOI: 10.1002/jmv.23772
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of HIV‐1 and surveillance of transmitted drug resistance variants among treatment Naïve patients, 5 years after active introduction of HAART in Kuala Lumpur, Malaysia

Abstract: Expansion of antiretroviral treatment programs have led to the growing concern for the development of antiretroviral drug resistance. The aims were to assess the prevalence of drug resistant HIV-1 variants and to identify circulating subtypes among HAART-naïve patients. Plasma specimens from N = 100 HIV+ HAART-naïve adult were collected between March 2008 and August 2010 and viral RNA were extracted for nested PCR and sequenced. PR-RT sequences were protein aligned and checked for transmitted drug resistance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…On the other hand, 11 partial gag -PR (HXB2: 1753–2591, 834bp) and 2 RT gene (HXB2: 2476–3440, 966bp) sequences were also amplified. Transmitted antiretroviral drug resistance mutation was not detected in the population, similar to previous drug resistance surveillance studies reported among antiretroviral-naïve patients in the country [13,25]. Based on the neighbour-joining phylogenetic tree analysis, HIV-1 genotypes mainly co-circulating in the region including CRF01_AE was detected among 40.9% (n = 61) of the blood donors, followed by CRF33_01B (n = 32, 21.5%) and subtype B (n = 15, 10.1%, including the subtype B variant of Thai origin, B') ( Fig 1 ).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…On the other hand, 11 partial gag -PR (HXB2: 1753–2591, 834bp) and 2 RT gene (HXB2: 2476–3440, 966bp) sequences were also amplified. Transmitted antiretroviral drug resistance mutation was not detected in the population, similar to previous drug resistance surveillance studies reported among antiretroviral-naïve patients in the country [13,25]. Based on the neighbour-joining phylogenetic tree analysis, HIV-1 genotypes mainly co-circulating in the region including CRF01_AE was detected among 40.9% (n = 61) of the blood donors, followed by CRF33_01B (n = 32, 21.5%) and subtype B (n = 15, 10.1%, including the subtype B variant of Thai origin, B') ( Fig 1 ).…”
Section: Resultssupporting
confidence: 85%
“…Based on phylogenetic reconstruction of the partial gag-pol genes, we identified three main HIV-1 genotypes commonly circulating in various risk populations, including CRF01_AE, subtype B (including subtype B') and CRF33_01B [1315] which attributed to around 73% of the total HIV-1 infections among the blood donors. We observed a higher prevalence of the Western subtype B (around 10%) compared to subtype B', which was reportedly circulating predominantly among the MSM populations in the country and elsewhere in the region [13,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations